Pengaruh Model Pembelajaran PBL (problem based learning) Terhadap Keterampilan Proses Sains Siswa pada Materi Pencemaran Lingkungan Kelas X SMA Negeri 1 Kutacane - Mrs. Nursafiah; Rika Aswarita; Muhammad Yassir; Rima Melati (Universitas Islam Sumatera Utara, 2020)
This study aimed to identify the effect of the Problem Based Learning learning model on students' science process skills on environmental pollution material at SMA Negeri I Kutacane. This research uses an experimental method, conducted in April-May 2016/2017 academic year. The population in this study was class X students, totaling 240 students. The sample consisted of 68 students consisting of two classes, namely class X IPA1 with 34 students as the experimental class, and class X IPA2 with 34 students as the control class. Data was collected through pretest and posttest. Students' Science Process Skills analyze data using description questions that have met 10 indicators of science process skills. Then the results obtained from the study that there are differences in the Science Process Skills of students who follow the problem based learning model with students who follow the discussion method on environmental pollution material for class X SMA Negeri I Kutacane.